The Challenge of Islam Nusantara Against Terorism: Analysis Study of Islam Nusantara of Ulama NU Movement in Central Java - Mu'min, Ma'mun; Mufid, Fathul (LPPM IAIN Kudus, 2018)
The more widespread ideology in the era of global terrorism today has become a global concern, acts of terror committed national or transnational terrorists have been bad for the creation of a harmonious world order, pluralist and inclusive. Several countries collapse in the Middle East and Africa as well as the tense conditions in Poso has been the evidence of how acts of terror committed the terrorists do not recognize tribes, nations and religions. If this trend continues, then the life of mankind and civilization of the world will be damaged. Long before understanding terrorism rampant in Indonesia and the world, the scholars Walisongo through propaganda Islamiyah has offered the concept of Islam Nusantara, the moderate Islam that can adapt to the cultural heritage at the time. Islam Nusantara or moderate Islam is essentially Islam that gave mercy to all the worlds. These efforts Walisongo scholars ulama NU followed by the next generation until now. Rampant ideology of terrorism today is of course a challenge for the NU clerics spearheading the development of Islam in the Indonesian archipelago. This research will find: formulation of basic normatively and historicity and the philosophical concept of Islam Nusantara, formulated the concept of Islam Nusantara in the perspective of scholars Walisongo and ulama NU in Central Java, the dynamics of socio-political development of Islam Nusantara in Central Java from time to time, the public response in Central Java to the development of Islam Nusantara, and the contribution of Islam Nusantara in a moderate Islam that can create harmony, pluralist and inclusive in order peaceful world civilization.